Multicultural Museum Education in and beyond Exhibit: Local and Transnational Synergies from Canada’s Oldest Chinatown - Chung, Tzu-I (Museum and Society, 2015)
In 2013, as part of ‘A Chinatown Celebration,’ a month-long festival celebrating Canada’s oldest Chinatown, the Royal BC Museum (RBCM) mounted a temporary exhibition Tradition in Felicities: Celebrating 155 Years of Victoria’s Chinatown TiF) (Figure 1). The exhibit also celebrated the Chinese Freemasons’ 150 anniversary in Canada. TiF featured a unique centerpiece: a handcrafted lantern created in the 1930s by Victoria’s Chinese Freemasons, one of the oldest Chinese organizations in Canada (Figure 2). It is the oldest-known such lantern in North America and Southeast Asia. ‘Objects,’ as scholars of material culture point out, ‘help [people] to know, understand, and situate [them]selves within the world, both externally and internally’(Clouse 2008: 6). The connections of objects to lived experiences render them historically and culturally meaningful. In tracing the history of the lantern, we consulted both members of the Chinese Freemasons, including elder Jon Joe who helped to identify the names listed on the lantern, and Chinatown’s former residents and descendants, in accordance with the RBCM’s practice of multicultural community outreach and participation.